DOES VERBAL ABILITY PREDICT AGEISM?. (11th November 2018) - Intrieri, R; Dunterman, R; Newell, C; Smiley, K
Abstract: Research examining the association between cognitive abilities and prejudice has focused on groups with low power and status. Of the meta-analyses that have assessed these relationships, none have focused on ageism. The current study examined the relationship between verbal ability and ageism. A Vocabulary score was created from the 40 question Shipley Institute of Living Scale (SILS). Participants completed the SILS followed by the Aging Semantic Differential, Facts on Aging Quiz (FAQ), and the Fraboni Scale of Ageism (FSA). The convenience sample consisted of 471 undergraduate students, with a mean age of 19.68 (SD= 2.278). A Hierarchical regression model was used to examine how well the SILS and the FAQ predicted ageist attitudes while controlling for biological sex and age. Results from the regression using ASD as the dependent variable was statistically significant F(4, 466) = 6.353, p<0.0001, R2 = .05 with Verbal Ability (SILS) β = 0.136, p = 0.005 and knowledge of aging (FAQ) β = -0.202, p < 0.0001 as significant predictors. Similar significant results were obtained using FSA as the dependent variable (F(4, 466) = 17.518, p<0.0001, R2 = .131 with sex β = -0.112, p = 0.012 and knowledge of aging (FAQ) β = -0.341, p < 0.0001 as significant predictors. These results indicate that individuals with greater knowledge of aging endorsed significantly lower ageist bias. Additionally, results show that higher verbal ability is likely to show greater ageist bias, contrary to theoretical expectations.